Pintoi Peanut: A Seed-Propagated Perennial Peanut Forage Option for Florida - Joao D. Sanchez; Joao Vendramini; Maria L. Silveira; Jose Dubeux Jr.; Lynn Sollenberger; Philipe Moriel (EDIS, 2020)
Because of its adaptability to Florida’s environmental conditions and ability to produce viable seeds, pintoi peanut represents an interesting forage alternative for cow-calf producers in the state. This 5-page document provides current information on pintoi peanut for forage and livestock producers in Florida. Written by Joao M. D. Sanchez, Joao Vendramini, Maria L. Silveira, Jose C. B. Dubeux Jr., Lynn E. Sollenberger, and Philipe Moriel, and published by the UF/IFAS Agronomy Department, November 2020.